Green synthesis of iron oxide nanoparticles for biomedical application and environmental remediation: a review - Akintelu, Sunday Adewale; Oyebamiji, Abel Kolawole; Olugbeko, Seyifunmi Charles; Folorunso, Aderonke Similoluwa (Eclética Química, 2021)
Ferrous oxide nanoparticles (IONPs) formed from plant materials have been considered as chemically friendly materials and have offered extensive applications. The distinctive features of IONPs, such as biocompatibility, low toxicity, catalytic behavior and multi reaction mechanism, have embodied them as good candidate for several biomedical applications. However, the synthesis of IONPs using plant extracts is gaining high popularity and recommendations because plant extracts could act as reducing and stabilizing agents during the process of synthesis. Furthermore, the biological method of synthesizing IONPs using plant extract offer some benefits, such as being simple, economic, environmentally friendly and require less energy when compared with both physical and chemical methods of synthesis. Hence, this review significantly summarized the synthesis, optimum conditions and characterization techniques involved in the synthesis of IONPs using several plant extracts. Consequently, comprehensive information about the applications of green synthesized IONPs as antimicrobial and anticancer therapeutic agents were well presented. The effectiveness of IONPs in environmental treatment of effluent containing dyes and other toxic agents were also properly discussed.